PENGARUH RETURN ON EQUITY, DEBT EQUITY RATIO, DAN SALES GROWTH TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN SEKTOR INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI TAHUN 2017-2020. - Nilam Anjani; Agus Eko Sutriyono; Hasanah Hasanah (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2022)
This study aims to analyze the effect of Return On Equity (ROE), Debt Equity Ratio (DER), and Sales Growth on tax avoidance in food and beverage industry companies listed on the Indonesia Stock Exchange for the 2017-2020 period. Tax Avoidance is the dependent variable in this study measured by the Effective Tax Rate. The independent variables studied include Return On Equity which is proxied by profitability, Debt Equity Ratio is proxied by Leverage, and Sales Growth. The sampling technique was carried out using purposive sampling there were 16 companies that met the criteria and data analysis was carried out using multiple linear regression using SPSS 24. The results showed that partially: (1) profitability had an effect on tax avoidance, (2) leverage had no effect on tax avoidance. tax avoidance, (3) sales growth has no effect on tax avoidance, (4) profitability, leverage, and sales growth simultaneously affect tax avoidance.